e-Module Development Instruments on The Topic of Free-range Chicken Eggs Productivity as Lessons for The Covid-19 Pandemic Era - K Anom W; Made Sukaryawan; Jejem Mujamil; Eka Ad'hiya (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
e-Module Development Instruments on the Topic of Free-range Chicken Eggs Productivity as Lessons for the Covid-19 Pandemic Era. This study aims to produce an e-Module Development instrument for Integrated Chemistry Learning STEM Subject Entrepreneurship TopicThe Productivity of Free-range Chicken Eggs as a Lesson in the Era of the Covid-19 Pandemic, valid and practical. This research is a type of development research, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) combined with the evaluation of the Tessmer formative test. The subjects of this research were lecturers and students of Chemistry Education Faculty of Teacher Training and Education, Universitas Sriwijaya. Tessmer's formative test consists of an expert review stage producing an average Aiken's coefficient value of 0.90; 0.93; and 0.94 in the high category, for each instrument validation score of material, pedagogy, and practicality. The one to one and small group test stages are carried out by obtaining qualitative input from student respondents as users. The results showed that the resulting e-module validation instrument had met the valid and practical criteria.Keywords: e-module, Free-range Chicken, covid-19DOI: 10.23960/jppk.v10.i3.2021.18